(untitled) (Scientific journal of the Fergana State University, 2025)
This article examines the effectiveness of endurance training and its impact on the physical development of 11-14-year-old students. The study results indicate that such training plays a significant role in enhancing endurance, strength, and respiratory function among children. An individualized approach adapted to students’ needs contributes to increasing motivation and improving overall physical activity levels